2011
DOI: 10.1021/ic2002964
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses, Crystal Structures, Transport Properties and First-Principles Electronic Structure Study of the (tTTF)2X (X = Br, I) Low-Dimensional Antiferromagnets

Abstract: An efficient synthetic procedure for the preparation of unsymmetrically substituted tetrathiafulvalene (TTF) donors has been used to obtain the trimethylene-tetrathiafulvalene (tTTF) donor with high purity. Good quality crystals of the two (tTTF)(2)X (X = Br, I) salts have been obtained by electrocrystallization. The two salts are isomorphous and contain tTTF layers which are built from (tTTF)(2) dimeric units. Both systems are low-dimensional antiferromagnets with the highest Néel temperatures for TTF based r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…Following this route, DMtTTF was prepared in pure form and in 53% yield, without need for tedious chromatographic separations, from 4,5-dimethyl-1, 3-dithiolium iodide and trimethylene-2-piperidyl-1,3-dithiolium hexafluorophosphate. [33,34] The electrocrystallizations of DMtTTF in 1,1,2-trichloroethane with the ClO 4 -and ReO 4 -anions afforded the 2 : 1 phases described earlier, [6,7] which crystallize in the monoclinic system, space group C2/c. As shown in Fig.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…Following this route, DMtTTF was prepared in pure form and in 53% yield, without need for tedious chromatographic separations, from 4,5-dimethyl-1, 3-dithiolium iodide and trimethylene-2-piperidyl-1,3-dithiolium hexafluorophosphate. [33,34] The electrocrystallizations of DMtTTF in 1,1,2-trichloroethane with the ClO 4 -and ReO 4 -anions afforded the 2 : 1 phases described earlier, [6,7] which crystallize in the monoclinic system, space group C2/c. As shown in Fig.…”
Section: Resultsmentioning
confidence: 85%
“…Both starting materials are stable in the reaction conditions and do not afford any symmetrical TTFs. Following this route, DMtTTF was prepared in pure form and in 53% yield, without need for tedious chromatographic separations, from 4,5‐dimethyl‐1,3‐dithiolium iodide and trimethylene‐2‐piperidyl‐1,3‐dithiolium hexafluorophosphate …”
Section: Resultsmentioning
confidence: 99%
“…We did not repeat the calculations for the solid, but instead we carried out calculations for selected dimers representative of the intra‐ and interstack interactions. We found that the intrastack interaction is strongly antiferromagnetic for an organic system,12 ( J =−213 cm −1 ), whereas all interstack interactions are extremely small (<0.1 cm −1 ). These calculations thus confirm that the system is in fact a 1D system with strong AF interactions between dimers within the π stacks and weak interstack interactions.…”
mentioning
confidence: 81%
“…The high-purity donor molecule tTTF was synthesized according to our original procedure described previously for the preparation of (tTTF)2X (X = Cl, Br, I) halide salts [18].…”
Section: Methodsmentioning
confidence: 99%